Update on Ppar𝜸 and Nonalcoholic Fatty Liver Disease - Gene P. Ables (PPAR Research)
Nonalcoholic fatty liver disease (NAFLD) is the most common initial presentation of obesity and insulin resistance. Uninterrupted progression of hepatic lipid accumulation often leads to fatty liver disease and eventually cirrhosis. Insulin resistance is one of the characteristics of type 2 diabetes. Several types of treatment have been employed against type 2 diabetes some of which ameliorate NAFLD. The frequent line of treatment to improve insulin sensitivity is the use of thiazolidinediones (TZD) which activate the nuclear receptor, peroxisome proliferator activated receptor gamma (Pparγ). Although TZDs are proven to be very effective in promoting insulin sensitivity, its actions on Pparγ have been complicated, specifically on NAFLD. According to studies in different models, Pparγ manifests both beneficial and undesirable effects on NAFLD. This paper will focus on the current knowledge of Pparγ and its effect on NAFLD.